KEHIDUPAN SOSIAL EKONOMI PETANI COKLAT DI DESA BETUMONGA KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI TAHUN (2003-2012) - -, Merliana - (Pendidikan Sejarah, 2014)
In mentawai regency begin to grow cocoa tree but the lack of infomation how the ways to grow and maintenance also minus of cocoa seeds so that the growth of cocoa trees do not grow well. As the people have understood by opening the cocoa tree fields it is the source income family especially the famer in Betumonga village. The purpose of this research is to explain the growth of the farmers in Betumonga village.The using method in the research are history method by steps such as heuristik critib source descript the result of research in the form of scription. The result of research indicate the effort of planting cocoa trees that are planted. The growth of cocoa trees too dephend on the sell of value cocoa in the markeu, the influence of the grwth of cocoa trees to social life of the farmers in Betumonga village kec north sipora period 2005-2012. It can be seen from the increase of income family farmers of cocoa Rp.188.000 per week become two hundred fifty seven hundree fifty thoushands rupiahs one iundred thoushands rupiah to one hundred twenty thousands rupiah per week it can be seen from the guality of housing and luxurious fa2ility such as electronic goods motor cycle etc, the change of daily consumption it can be seen from the education of people available new job sector for the farmers and increase the aware of the people to go public centre of health not use traditional medicines to recover from the sickness.